Body weight and mood state modifications in mixed martial arts: An exploratory pilot - Brandt R. (2018)
© 2018 National Strength and Conditioning Association.Mixed martial arts (MMA) fighters typically use rapid weight loss (RWL) as a strategy to make competition weight. The aim of the present study was to compare body weight and mood changes in professional male MMA athletes who used strategies to rapidly lose weight (n = 9) and with MMA athletes who did not (n = 3). Body mass and mood states of anger, confusion, depression, fatigue, tension, and vigor and total mood disturbance were assessed (a) 30 days before competition, (b) at the official weigh-in 1 day before competition, (c) 10 minutes before competition, and (d) 10 minutes postcompetition. Results indicated that RWL associated with reporting higher confusion and greater total mood disturbance at each assessment point. Rapid weight loss also associated with high anger at the official weigh-in. However, in performance, RWL did not have deleterious effects on performance. The RWL group also reported greater total mood disturbance at all assessment points with a moderate difference effect size. Research supports the notion that RWL associates with potentially dysfunctional mood states.